1975
DOI: 10.1002/aja.1001440305
|View full text |Cite
|
Sign up to set email alerts
|

Periodic fibrillar material in intracellular vesicles and in electron‐dense bodies in chondrocytes of rat costal and tracheal cartilage at various ages

Abstract: The occurrence of intracellular fibrillar material (frequently banded) has been studied in normal costal and tracheal chondrocytes of rats at various ages ranging from 1 to 90 days. The study methods have included digestion with collagenase, electron histochemical techniques and routine electron microscopy. Banded fibrillar material has been observed intracellularly in vesicles or in electron-dense bodies in perichondrial and subperichondrial chondrocytes from rats of all ages. These fibrils and extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The presence of intracellular collagen-like material in Golgi saccules, vesicles, and vacuoles in mammalian chondrocytes reflects the involvement of these cells in collagen production (Sheldon and Kimball, 1962;Seegmiller et al, 1972;Dearden, 1975). There was, however, no evidence to suggest that lamprey chondrocytes are involved in collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intracellular collagen-like material in Golgi saccules, vesicles, and vacuoles in mammalian chondrocytes reflects the involvement of these cells in collagen production (Sheldon and Kimball, 1962;Seegmiller et al, 1972;Dearden, 1975). There was, however, no evidence to suggest that lamprey chondrocytes are involved in collagen production.…”
Section: Discussionmentioning
confidence: 99%
“…Emergence of Chondrocytes in Serum-free Culture sisted of a loose meshwork of faintly banded collagen fibrils that were 19 nM in diameter . Ruthenium red-stained granules (putative proteoglycans) (2,15,16,19,21,33,34,38,46,53,55) 20-30 nM in diameter were associated with many of the collagen fibrils ( Fig. 3) and with the cell surfaces.…”
Section: Evidence For Cell Proliferation In Primary Cultures and Subcmentioning
confidence: 99%
“…After a prolonged period in culture, most calvarium cells were seen to be chondrocytes associated with cartilage nodules. Ultrastructural examination of cultures maintained for 30 d in chemically defined medium revealed that the cells in the nodules were embedded in a dense extracellular matrix resembling the chondrocyte lacunae of native cartilage (15,53) . The extracellular matrix was composed of collagen fibrils which were faintly banded and averaged 19 nm in diameter.…”
Section: Proteoglycan Labeling In Primary and Secondary Culturesmentioning
confidence: 99%
“…The presence of periodic materials within the innermost Golgi cisterna strongly suggests that the materials represent a formative stage in a process of collagenogenesis. Similar intracytoplasmic structures were reported in other collagen-synthesizing cells, such as osteoblast, odontoblast, fibroblast, and fibrocartilage (Weinstock, 1972;Weinstock and Leblond, 1974;Dearden, 1975;Ghadially et al, 1978;Marchi and Leblond, 1983). Thus arises the question why do these structures, which appear in proliferating cells, engage in collagen formation?…”
Section: Discussionmentioning
confidence: 55%